2018
DOI: 10.1097/qad.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

HLA-associated polymorphisms in the HIV-2 capsid highlight key differences between HIV-1 and HIV-2 immune adaptation

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In our analysis, HIV-2 nonsynonymous evolutionary rates are an order of magnitude lower than the synonymous rates. Findings from a study of interhost evolution of HIV-2 p26 , showed little evidence of positive selection in HIV-2 p26 evolution (49). This is surprising as strong Gag-specific CTL responses are common in HIV-2 long-term non-progressors (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, HIV-2 nonsynonymous evolutionary rates are an order of magnitude lower than the synonymous rates. Findings from a study of interhost evolution of HIV-2 p26 , showed little evidence of positive selection in HIV-2 p26 evolution (49). This is surprising as strong Gag-specific CTL responses are common in HIV-2 long-term non-progressors (55).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether the signature amino acid variants identified by the VESPA analysis were associated with disease progression markers in a larger, external cohort. This was done by testing the association of these p26 amino acid variants with CD4% and HIV-2 plasma viral loads in 86 HIV-2 positive participants from the Caio cohort (23,49).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increased sensitivity of HIV-2 capsid to TRIM5α restriction, as well as the strong cytotoxic T cell response directed towards gag, there is no evidence of positive selection pressure on gag divergence in a crosssectional analysis of viral sequences from the Caió community cohort [59]. Purifying selection pressure predominates in interhost evolution, and this reflects the constrained evolution of this gene.…”
Section: The Importance Of Gagmentioning
confidence: 93%
“…The interaction between the viral capsid, host restriction factors and the cellular immune response may be central to maintaining durable control of viral replication in HIV-2 infection. HIV-2-specific CTL may be able to control viral replication and maintain a low level of immune activation for many years, without the emergence of viral escape mutants [59]. During this process, HIV-2 capsids enriched in proline residues may favour the efficient processing of CTL epitopes that are associated with a long-lasting, protective gag-specific CTL response.…”
Section: Conclusion: Possible Causal Factors Which Promote Hiv-2 Disementioning
confidence: 99%
See 1 more Smart Citation